A Color Topographic Map Based on the Dichromatic Reflectance Model. (24th April 2008) - Gouiffès, Michèle; Zavidovique, Bertrand
Abstract : Topographic maps are an interesting alternative to edge-based techniques common in computer vision applications. Indeed, unlike edges, level lines are closed and less sensitive to external parameters. They provide a compact geometrical representation of images and they are, to some extent, robust to contrast changes. The aim of this paper is to propose a novel and vectorial representation of color topographic maps. In contrast with existing color topographic maps, it does not require any color conversion. For this purpose, our technique refers to the dichromatic reflectance model, which explains the distribution of colors as the mixture of two reflectance components, related either to the body or to the specular reflection. Thus, instead of defining the topographic map along the sole luminance direction in the RGB space, we propose to design color lines along each dominant color vector, from the body reflection. Experimental results show that this approach provides a better tradeoff between the compactness and the quality of a topographic map.